The New Normal : A Sector-level Perspective on Productivity Trends in Advanced Economies - Dabla-Norris, Era (Staff Discussion Notes; Staff Discussion Notes ;, 2015)
Total factor productivity growth was stagnant or slowing in many advanced countries even prior to the crisis. This paper documents sector-level productivity patterns across advanced economies prior to the crisis and examines the role of product and labor market rigidities as well as innovation and investments in information technology and human capital in driving productivity differences across sectors and countries. Since productivity payoffs of reforms evolve over time, we also focus on large changes in the structural indicators examine their dynamic impact on productivity, employment, and output. Our results suggest that reform priorities depend on country-specific settings, including the scale of specific policy distortions and the distance from the technology frontier. Productivity gains from reforms are large and materialize predominantly in the medium term, with some important variations across industries and countries.